2020
DOI: 10.1186/s12864-020-6567-3
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput deep sequencing reveals the important role that microRNAs play in the salt response in sweet potato (Ipomoea batatas L.)

Abstract: Background: MicroRNAs (miRNAs), a class of small regulatory RNAs, have been proven to play important roles in plant growth, development and stress responses. Sweet potato (Ipomoea batatas L.) is an important food and industrial crop that ranks seventh in staple food production. However, the regulatory mechanism of miRNAmediated abiotic stress response in sweet potato remains unclear. Results: In this study, we employed deep sequencing to identify both conserved and novel miRNAs from salinityexposed sweet potat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 94 publications
9
47
0
Order By: Relevance
“…Nitrogen starvation [149] miR156, miR164, miR167, miR168, miR528, miR820, miR821, miR1318 Low-nitrogen stress [150] multiple miRNAs Abiotic stress [151] osa-miR414, osa-miR164e, osa-miR408 Salt stress [152] Soybean (Glycine max) multiple miRNAs Water deficit [153] Sugarcane (Saccharum L.) multiple miRNAs Water-deficit stress [154] multiple miRNAs Low temperature stress [155] multiple miRNAs Waterlogging condition [156] multiple miRNAs Drought stress [157] multiple miRNAs Drought stress [158] Sweet Potato (Ipomoea batatas) multiple miRNAs Drought and CO 2 stress [159] multiple miRNAs Salt stress [160] Switchgrass (Panicum virgatum) multiple miRNAs Drought and heat stress [161] multiple miRNAs Salt stress [162] Tobacco (Nicotiana tabacum) multiple miRNAs Salt and alkali stress [163] Tomato (Solanum lycopersicum) multiple miRNAs Drought and heat stress [164] multiple miRNAs Drought stress [165] Turnip (Brassica rapa) miR166h-3p-1, miR398b-3p, miR398b-3p-1, miR408d, miR156a-5p, miR396h, miR845a-1, miR166u, Bra-novel-miR3153-5p and Bra-novel-miR3172-5p…”
Section: Micrornas Stress Responses Referencementioning
confidence: 99%
“…Nitrogen starvation [149] miR156, miR164, miR167, miR168, miR528, miR820, miR821, miR1318 Low-nitrogen stress [150] multiple miRNAs Abiotic stress [151] osa-miR414, osa-miR164e, osa-miR408 Salt stress [152] Soybean (Glycine max) multiple miRNAs Water deficit [153] Sugarcane (Saccharum L.) multiple miRNAs Water-deficit stress [154] multiple miRNAs Low temperature stress [155] multiple miRNAs Waterlogging condition [156] multiple miRNAs Drought stress [157] multiple miRNAs Drought stress [158] Sweet Potato (Ipomoea batatas) multiple miRNAs Drought and CO 2 stress [159] multiple miRNAs Salt stress [160] Switchgrass (Panicum virgatum) multiple miRNAs Drought and heat stress [161] multiple miRNAs Salt stress [162] Tobacco (Nicotiana tabacum) multiple miRNAs Salt and alkali stress [163] Tomato (Solanum lycopersicum) multiple miRNAs Drought and heat stress [164] multiple miRNAs Drought stress [165] Turnip (Brassica rapa) miR166h-3p-1, miR398b-3p, miR398b-3p-1, miR408d, miR156a-5p, miR396h, miR845a-1, miR166u, Bra-novel-miR3153-5p and Bra-novel-miR3172-5p…”
Section: Micrornas Stress Responses Referencementioning
confidence: 99%
“…When the seedlings had five to six functional leaves and adventitious roots of 8 to 10 cm, these seedlings were subjected to six different stresses, respectively. To study the expression patterns under these stresses, the adventitious roots of seedlings were submerged in the solution containing 150 mM NaCl, 20% PEG 6000, 100 mM ABA, 50 mg/L uniconazole, and 50 mg/L gibberellic acid (GA 3 ) respectively [ 54 ]. For black spot pathogen treatment, C. fimbriata conidia was collected after growing in potato dextrose agar (PDA) at 28 °C for 7 days, then were diluted to 1 × 10 4 spores/mL with sterile water, and then the roots of sweetpotato seedlings were cultivated in the 1 × 10 4 spores/mL conidia suspension.…”
Section: Methodsmentioning
confidence: 99%
“…Fu et al identified 1,077 miRNAs in Zea mays, comprising the highest number of identified miRNAs in various crops among the reports (Fu et al, 2017). Moreover, 882, 876, 693, and 650 miRNAs were identified in Mesembryanthemum crystallinum, Medicago truncatula, Vicia faba, and Ipomoea batatas, respectively (Jian et al, 2016;Cao et al, 2018;Alzahrani et al, 2019;Yang et al, 2020). The numbers of identified miRNA vary from dozens to hundreds, which may be due to the plant species, tissue specificity, development stage, and salt stress treatment methods.…”
Section: Identification and Expression Of Plant Mirnas Under Salt Stressmentioning
confidence: 99%